2009
DOI: 10.1159/000252833
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Nodular Gastritis in Dyspeptic Adults: Prevalence and Association with <i>Helicobacter pylori</i> Infection

Abstract: Objective: To determine the prevalence and histological features of endoscopic nodular gastritis (NG) in adult dyspeptic patients and its relation to Helicobacter pylori infection. Subjects and Methods: A retrospective endoscopic report review of 2,142 patients identified 67 patients with NG during the period from 1 September 2006 to 31 August 2007. A subset of 32 NG patients (group 1) who had had gastric biopsies during upper gastrointestinal endoscopy and had been evaluated for H. pylori infection were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
1
17
0
2
Order By: Relevance
“…In the present study, asymptomatic NG was frequent in young adults and females and was found in 2% of patients who received screening EGDs, in keeping with the results of Chen et al [10] and Al-Enezi et al [21]. However, it was previously observed that the prevalence of NG was variable and ranged from 0.05 to 66.3% in H. pylori-infected patients ( Table 6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, asymptomatic NG was frequent in young adults and females and was found in 2% of patients who received screening EGDs, in keeping with the results of Chen et al [10] and Al-Enezi et al [21]. However, it was previously observed that the prevalence of NG was variable and ranged from 0.05 to 66.3% in H. pylori-infected patients ( Table 6).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, NG has also been reported in adult dyspeptic patients with H. pylori infection [3] and in patients with H. pylori-related diseases, such as gastroduodenal ulceration and gastric cancer [4,19,20]. As the clinical significance of NG comes to the fore, the clinicoepidemiological characteristics of NG in patients who underwent endoscopy for the evaluation of upper gastrointestinal symptoms have been revealed [3,6,9,10,21,22], and it has been recommended that symptomatic NG patients should receive H. pylori eradication treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These isolates [by polymerase chain reaction (PCR)] were recovered from 101 Turkish children (53 girls and 48 boys, ranging between 4 and 18 years old, average 12 years) who underwent upper gastrointestinal endoscopy with abdominal symptoms at the clinic of the Pediatric Gastroenterology Department at the Firat University Hospital between March 2011 and September 2012. Antral nodularity was defined as being endoscopically characterized by the irregular appearance of the mucosa as like that of a "cobblestone pavement" [14] . Also, the presence of ulcers was determined by endoscopic examination.…”
Section: Methodsmentioning
confidence: 99%
“…The minimum of both H. pylori density and inflammatory changes was observed in the most distal part of the corpus at the greater curvature [23,24]. A positive correlation between high histological gastritis score and high density of H. pylori was also demonstrated in cases of nodular gastritis in adults as well as in children, where this typical endoscopic representation of disease is more common [25,26]. Marked CD4 (Th cell marker) and CD19 (B cell marker) positive inflammatory cell infiltration is concomitant in cases with a high histological grade of gastritis and high density of H. pylori, suggesting predominance of a humoral type immune response rather than a cytotoxic response.…”
Section: Histological Determination Of Bacterial Density and Grade Ofmentioning
confidence: 99%